2013
DOI: 10.1186/1471-2334-13-60
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of Hepatitis C virus infection in Brazil, 2005 through 2009: a cross-sectional study

Abstract: BackgroundHepatitis C chronic liver disease is a major cause of liver transplant in developed countries. This article reports the first nationwide population-based survey conducted to estimate the seroprevalence of HCV antibodies and associated risk factors in the urban population of Brazil.MethodsThe cross sectional study was conducted in all Brazilian macro-regions from 2005 to 2009, as a stratified multistage cluster sample of 19,503 inhabitants aged between 10 and 69 years, representing individuals living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
5
24

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(188 citation statements)
references
References 34 publications
9
150
5
24
Order By: Relevance
“…The study shows remarkably similar results to the main LAC study on hepatitis prevalence, the Brazilian National Prevalence Study [24], which shows lower than usually reported prevalence, wide regional heterogeneity, injected and sniffed drug abuse, and a major role for hospitalizations and glass syringe injections, among other risk factors related to social circumstances (such as lack of sewage disposal). Brazil national study concludes that known risk factors explain only 50% of hepatitis C cases.…”
Section: Resultssupporting
confidence: 67%
“…The study shows remarkably similar results to the main LAC study on hepatitis prevalence, the Brazilian National Prevalence Study [24], which shows lower than usually reported prevalence, wide regional heterogeneity, injected and sniffed drug abuse, and a major role for hospitalizations and glass syringe injections, among other risk factors related to social circumstances (such as lack of sewage disposal). Brazil national study concludes that known risk factors explain only 50% of hepatitis C cases.…”
Section: Resultssupporting
confidence: 67%
“…The opposite situation occurred in Brazil, as our fi ndings revealed an increase in the incidence rates of hepatitis C during our analysis period. This may be due to the underreporting of hepatitis C by some surveillance systems, which has been a topic of discussion in Europe and the United States (20) . A study developed in Poland sought to assess the epidemiological situation of hepatitis C in 2011 and compare it to previous years.…”
Section: Methodsmentioning
confidence: 99%
“…These fi ndings are consistent with our study. The burden of infection in Brazil, in absolute terms, shows an unequal geographical distribution, with the highest concentrations in the South and Southeast, compared to lower rates in the North, Northeast, and Midwest, between 2003 and 2009 (20) . A likely explanation for the higher incidence rates in the South and Southeast may be better access to the health care systems in these regions, which are more organized (21) .…”
Section: Methodsmentioning
confidence: 99%
“…In a population-based study conducted in 1998 in Salvador, the capital of the northeastern State of Bahia, the HCV prevalence was 1.5%. (12) Several studies in Brazil have reported that HCV genotype 1 is more prevalent than genotype 3 among patients who had received a blood transfusion. (13) The first report on the HCV genotype distribution in Salvador -Bahia in intravenous drug users (IDU´s) showed a high prevalence in genotype 1, followed by genotype 3.…”
Section: Hcv Biologymentioning
confidence: 99%